Assess the reality of the efficiency of the spatial distribution of health services in Aqrah district - Mohammed, Shaima A.; Mohammed, Ahmed A (Academic Journal of Nawroz University, 2021)
The study aims to identify the reality of spatial distribution of health services in Aqra district and their compatibility with health planning standards. The study relied on the descriptive analytical approach and the quantitative approach based on the Geographic Information System (GIS). And that the most important finding of the study is the presence of a shortage of staff from doctors and nurses in addition to the pattern of distribution of health services is the random pattern and the absence of consideration for the planning criteria in the distribution of health services. The study recommended the necessity of filling the shortage in the medical staff and the need to use the (GIS) system for future planning to choose the best and most appropriate new sites for health services to achieve a fair distribution between the residents of the region.